2007
DOI: 10.1016/j.neuroimage.2006.12.038
|View full text |Cite
|
Sign up to set email alerts
|

Social stimuli interfere with cognitive control in autism

Abstract: Autism spectrum disorders are characterized by cognitive control deficits as well as impairments in social interactions. However, the brain mechanisms mediating the interactive effects of these deficits have not been addressed. We employed event-related functional magnetic resonance imaging (fMRI) to examine the effects of processing directional information from faces on activity within brain regions mediating cognitive control. High-functioning individuals with autism and age-, gender-, and IQ-matched neuroty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
81
3
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(96 citation statements)
references
References 79 publications
11
81
3
1
Order By: Relevance
“…Hence, in contrast to incongruent gaze cues, which triggered spatial attention shifts, congruent gazes toward the target elicited processes that may be more related to the interpretation of the visual scene (two people looking at the target together). Most importantly, both main contrasts of gaze cues replicate earlier findings (Bristow et al, 2007;Dichter & Belger, 2007;Pelphrey et al, 2003;Schilbach et al, 2010) and-together with our behavioral findings-indicate that the present paradigm successfully induced gaze following.…”
Section: Gaze Congruencysupporting
confidence: 90%
“…Hence, in contrast to incongruent gaze cues, which triggered spatial attention shifts, congruent gazes toward the target elicited processes that may be more related to the interpretation of the visual scene (two people looking at the target together). Most importantly, both main contrasts of gaze cues replicate earlier findings (Bristow et al, 2007;Dichter & Belger, 2007;Pelphrey et al, 2003;Schilbach et al, 2010) and-together with our behavioral findings-indicate that the present paradigm successfully induced gaze following.…”
Section: Gaze Congruencysupporting
confidence: 90%
“…This would have allowed us to exclude the possibility that the observed group difference is due to a non-social effect, that is, the mere observation of (non-biological) movement as compared to when no movement is observed (baseline condition). However, a previous study showed that individuals with ASD show no difference as compared to control individuals in the brain activity in response to non-social arrows in the flanker task (Dichter & Belger, 2007). Moreover, interference tasks that included non-social control conditions did not observe differences for ASD individuals within these 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 conditions (Gowen et al, 2008), which suggest that they generally have no heightened sensitivity for non-social conditions.…”
Section: The Effect Of Perception On Action: Rp Resultsmentioning
confidence: 92%
“…Moreover, some studies support a brain functional overlap between the aforesaid 'social regions' and other neurocognitive processes, These include autobiographical memory processing (Cabeza et al 2004;Markowitsch et al 2000;Spreng et al 2009), which is commonly impaired in patients with ASD Crane and Goddard 2008;Lind and Bowler 2010), as well as motor processing (Allen and Courchesne 2003;Allen et al 2004;Brieber et al 2010;Dinstein et al 2010;Martineau et al 2010;Mizuno et al 2006;Mostofsky et al 2009;Muller et al 2001Muller et al , 2003Muller et al , 2004Villalobos et al 2005) and attention processing (Dichter and Belger 2007). These data suggest a common neuroanatomical substrate for all these ASD deficits (Mostofsky et al 2009).…”
Section: Discussionmentioning
confidence: 87%